Synthesis and characterization of polyetherimides containing multiple ether linkages and pendent pentadecyl chains - Tawade, Bhausaheb V.; Kulkarni, Arun D.; Wadgaonkar, Prakash P. (Polymer International, 2015)
4-(4-(4-(4-Aminophenoxy)-2-pentadecylphenoxy)phenoxy)aniline (APPPA) was synthesized starting from cashew nut shell liquid-derived bisphenol, i.e. 4-(4-hydroxyphenoxy)-3-pentadecylphenol, by nucleophilic substitution reaction with 4-chloronitrobenzene followed by reduction of the formed 4-(4-nitrophenoxy)-1-(4-(4-nitrophenoxy)phenoxy)-2-pentadecylbenzene. Three new polyetherimides containing multiple ether linkages and pendent pentadecyl chains were synthesized by one-step high-temperature solution polycondensation of APPPA in m-cresol with three aromatic dianhydrides, i.e. 3,3,4,4-oxydiphthalic anhydride, 4,4-(hexafluoroisopropylidene)diphthalic anhydride and 3,3,4,4-biphenyltetracarboxylic dianhydride. Inherent viscosities and number-average molecular weights of the polyetherimides were in the ranges 0.66-0.70 dLg(-1) and 17100-29700gmol(-1) (gel permeation chromatography, polystyrene standards), respectively, indicating the formation of reasonably high molecular weight polymers. The polyetherimides were soluble in organic solvents such as chloroform, dichloromethane, tetrahydrofuran, pyridine, m-cresol, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethylsulfoxide, and could be cast into transparent, flexible and tough films from their solutions in chloroform. The polyetherimides exhibited glass transition temperatures (T-g) in the range 113-131 degrees C. The lowering of T-g could be attributed to the combined influence of flexibilizing ether linkages and pentadecyl chains which act as packing-disruptive' groups. The temperature at 10% weight loss (T-10), determined from thermogravimetric analysis in nitrogen atmosphere, was in the range 460-470 degrees C demonstrating good thermal stability. The virtues of solubility and large gap between T-g and T-10 mean that the polyetherimides containing pendent pentadecyl chains have possibilities for both solution as well as melt processability. (c) 2015 Society of Chemical Industry
Keywords: CNSL; ether linkage; pentadecyl; polyetherimide; processability

Step-growth polymers from cashew nut shell liquid (CNSL)-based aromatic difunctional monomers - Chatterjee, Deepshikha; Sadavarte, Nilakshi V.; Shingte, Rahul D.; More, Arvind S.; Tawade, Bhausaheb V.; Kulkarni, Arun D.; Ichake, Amol B.; Avadhani, C. V.; Wadgaonkar, Prakash P. (Cashew Nut Shell Liquid, 2017)
Cashew nut shell liquid (CNSL) is an attractive renewable resource material which is available in abundance (44,50,000 tonnes worldwide and 7,53,000 tonnes in India in 2013) at low cost (around 0.27 $/kg in 2015) and is mainly composed of anacardic acid, cardanol, cardol and 2-methyl cardol. Cardanol is obtained as a major product during hot oil extraction or roasting process of CNSL. Cardanol possesses interesting structural features. The aromatic ring of cardanol can undergo electrophilic substitution reactions; the unsaturated side chain can undergo epoxidation, hydrogenation, metathesis, etc., while the phenolic hydroxyl group can undergo various reactions such as esterification and alkylation. Such opportunities of chemical modifications offered by cardanol have been extensively explored to synthesise a range of interesting aromatic difunctional monomers that have subsequently been utilised to prepare a host of step-growth polymers. Summarised herein are research efforts that have contributed towards the synthesis of step-growth polymers based on aromatic difunctional monomers derived from cardanol. The properties of high-performance polymers, with a particular focus on processability and thermal characteristics, are highlighted.